Mens Rea and Narratives of Violence: The Guilty Mind in Twenty-First-Century American Literature - Wilson-Scott, Joanna (American Studies in Scandinavia, 2021)
This article presents two twenty-first-century novels that deal with particularly charged and contemporary expressions of violence in the United States: Matthew Quick’s Forgive Me, Leonard Peacock and the threat of armed students in school, and John Updike’s Terrorist and the threat of Islamic extremism. High profile acts of violence of this kind in the United States leading up to and into the years following the turn of the millennium prompted significant concern surrounding the identification of would-be perpetrators, including those in the premeditating stage of their intended attacks. This article argues that stepping away from the violent act and focusing instead on the violent mind situates premeditation as an integral part of violence and its conceptualization. Further, interest in the internalized aspects of violence can be seen as a response to very real socio-cultural concerns in the United States. In order to achieve this analytical focus, the article adopts the legal concepts of mens rea (the guilty mind) and actus reus (the guilty act), interweaving them with literary criticism in order to suggest that novels can serve as Momusian windows into the premeditating stage of violence through immersion into the violent mind. In so doing, they contribute more robustly to broader understandings of violence in the United States as it evolves from concept to action.